Late Variscan remagnetization of Devonian carbonates in the Moravo-Silesian zone (Czech Republic): implications for dating tectonic deformation - Grabowski, J.; Babek, O.; Hladil, J.; Pruner, P.; Schnabl, P.; Werner, T.; Gersl, M.; Otava, J. (TRABAJOS DE GEOLOGÍA, 2009)
New paleomagnetic data from the Moravo-Silesian Zone (Eastern Variscides, Czech Republic) confirmed the presence of strong Late Variscan overprint. Data from four localities indicate syn-folding to post-folding age of remagnetization, which was acquired throughout a time span between 335-288 Ma. This implicates that deformation in the area started as early as the Visean (Lower Carboniferous) and continued to the lowermost Permian. Remagnetization was coeval with the same process reported from Ardennes and partially also Cantabrian arc.